A new species of Paraxantia Liu & Kang (Orthoptera: Tettigoniidae; Phaneropterinae; Vosiini) from China - Wu, Chao; Liu, Chun-Xiang (Zootaxa, 2021)
The genus Paraxantia Liu & Kang, 2009 previously included 10 species, which are endemic to south of China. Herein we describe one new species: P. hakka sp. nov. from Guangdong Province, China. Illustrations of male stridulatory files of most Paraxantia species are provided. The distribution of the new species is discussed and mapped. All types are deposited in Insect Collection of Institute of Zoology, Chinese Academy of Sciences, Beijing, China (IZCAS).